2015
DOI: 10.1111/jace.13485
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties and Thermally Stimulated Depolarization Currents of (1 − x)MgTiO3xCa0.8Sr0.2TiO3 Ceramics

Abstract: 1 -x)MgTiO 3 -xCa 0.8 Sr 0.2 TiO 3 (0.04 ≤ x ≤ 0.2, MT-CST) composite ceramics were prepared by the conventional solidstate reaction process. The phase composition, microwave dielectric properties, and microwave dielectric loss mechanisms were studied. Ca 0.8 Sr 0.2 TiO 3 was employed as a s f compensator for MgTiO 3 , and they coexisted well without forming any secondary phases. Interestingly, significant dielectric relaxations associated with oxygen vacancy defects were observed in all the MT-CST ceramics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
5
36
2
Order By: Relevance
“…For example, T m of TSDC curves associated with trap charge will decrease with the increasing of T p , whereas T m of TSDC curves related to oxygen vacancy will performed an increasing tendency with the climbing of T p . If the depolarization current density is caused by defect dipole, T m of TSDC curves will exhibit no dependence on T p . Therefore, TSDC was carried out to study the defect types and concentrations in the KNN‐based ceramics.…”
Section: Defect Analysis and Discussionmentioning
confidence: 99%
“…For example, T m of TSDC curves associated with trap charge will decrease with the increasing of T p , whereas T m of TSDC curves related to oxygen vacancy will performed an increasing tendency with the climbing of T p . If the depolarization current density is caused by defect dipole, T m of TSDC curves will exhibit no dependence on T p . Therefore, TSDC was carried out to study the defect types and concentrations in the KNN‐based ceramics.…”
Section: Defect Analysis and Discussionmentioning
confidence: 99%
“…A microwave dielectric ceramic should possess some stringent properties such as (a) high unloaded quality factor (Qnormalu×f) for better selectivity, (b) high relative permittivity ( ε r ) for miniaturization, (c) zero temperature coefficient of the resonant frequency ( τ f ) for temperature stability, and (d) low sintering temperature. The development of materials that combine all the above‐mentioned properties has become a key challenge for the electronic industry …”
Section: Introductionmentioning
confidence: 99%
“…The driving requirements for multifunctional communication systems with light weight and high performance have vigorously stimulated growing research on microwave dielectric materials that have a rapid development. Nowadays, the microwave dielectric ceramics have been widely applied to information or communication industries involving Wi‐Fi gadgets, mobile handheld devices, satellite communication systems, and avionics including civil and military radar system . Up to now, accumulated efforts have been paid to develop new microwave dielectric materials to meet the demands for integrated and intelligent application of the next generation of telecommunication products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential for materials to possess a relatively high dielectric permittivity (usually above 35). Recently, many new microwave dielectric ceramics have been developed to meet the explosive growth of wireless communication industry, e.g., (Ba 0.4 Sr 0.6 )TiO 3 ceramics, Ca[(Ga 1/2 Nb 1/2 ) 0.53 T i0.47 ]O 3 ceramics, Ba 0.6 Sr 0.4 La 4 Ti 4 O 15 –Ba 5 Nb 4 O 15 , and Co 0.5 Ti 0.5 NbO 4 ceramics, as well as (Mg 0.95 Ni 0.5 )Si 2 O 4 ceramic with Li 2 CO 3 –V 2 O 5. Nevertheless, the very microwave ceramics are still difficult to be found that satisfies multiple goals including low sintering temperature, high dielectric permittivity, and high‐quality factor Q × f , as well as near‐zero temperature coefficient of resonant frequency; in turn not fully satisfy the demands for some important communication microwave circuits.…”
Section: Introductionmentioning
confidence: 99%